Experimental and numerical investigations of the effect of pressure on combustion characteristics of Mg-based solid fuels. (1st December 2021) - Zhang, Kangkang; Han, Yuge; Ren, Dengfeng; Zhu, Chenguang
Highlights: Designed a small-scale negative pressure combustion experiment system. Revealed the effect of pressure on flame structure and temperature. Demonstrated the pressure sensitivity of the burning rate under 0.02–0.1 MPa. Predicted the combustion products distribution characteristics. Abstract: The present study is devoted to comprehensively evaluating the combustion performance of Mg-based (Magnesium/polytetrafluoroethylene/Viton) solid fuels in high-altitude operating environments. A small-scale sealed CO2 laser ignition experiment system is designed to produce different negative pressure environments. A high-speed camera (HSC) and an infrared thermal imager are used to cooperatively capture the burning process. The results obtained demonstrate that the area of the flame core zone and the flame temperature increase significantly as the pressure increases. It is conducive to the heat feedback of the gas phase reaction zone to the solid phase heating zone, resulting in an increase in the burning rate. As the Mg content increases, the flame temperature is decreased and the burning rate is increased. The burning rate for the Mg-based solid fuels is found to increase monotonically with ambient pressure and to follow the Vieille's law in the pressure range of 0.02–0.1 MPa. Based on the experiment, a three-dimensional combustion-flow coupling solution model is established including the detailed aerobic combustion reaction kinetic model and the eddy dissipation concept (EDC) model. Numerical simulation results reveal that the content of incompletely reacted Mg increases as the pressure decreases. Conversely, the decreasing behavior of oxygen partial pressure at low pressure reduces the probability of reaction of Mg with O2, resulting in a dramatical decrease in the mass fraction of MgO. The scientific findings provide useful insight for the deep understanding of the combustion behavior of Mg-based solid fuels, and support for the increasing demands for both military and civilian applications.